A Case of Tumour Twins: A Rare Presentation of Simultaneous Breast and Endometrial Malignancies - Sreenidhi Sreeram; Barathi Gunabooshanam; Vasugi Gramani Arumugam; Gouthaman (Journal of Clinical and Diagnostic Research)
The probability of simultaneous Breast Carcinoma (BC) and Endometrial Carcinoma (EC) in one person is extremely low and might be only a co-incidence. Hereby, the authors present a case report of a 62-year-old female presented to the Outpatient Department (OPD) with complaints of postmenopausal bleeding for a period of six months. On examination, her abdomen was enlarged, and a right breast mass was also noted incidentally. An ultrasound of the abdomen showed a thickened endometrium. A screening mammogram revealed a Breast Imaging-Reporting and Data System (BI-RADS) 4B lesion in the lower central quadrant of the right breast. Subsequently, an endometrial aspiration was done and showed features of atypical endometrial hyperplasia. A Tru-cut biopsy of the right breast mass was taken, showed features of a mucinous neoplasm favouring mucinous carcinoma, Nottingham’s histological grade 1. Immunohistochemistry (IHC) work-up favoured a Luminal A molecular subtype of mammary carcinoma. Magnetic Resonance Imaging (MRI) and Positron Emission Tomography (PET) imaging were also done which revealed a thickened endometrium with increased metabolic activity. Patient underwent a right Modified Radical Mastectomy (MRM), total abdominal hysterectomy with bilateral salpingo-oophorectomy, and lymph node sampling. Grossly, the MRM specimen showed a single, grey-white, firm, infiltrative lesion measuring 2.2×2.2×1.5 cm in the lower central quadrant. Microscopy showed a neoplastic tissue composed of nests of tumour cells floating in lakes of abundant extracellular mucin. The hysterectomy specimen revealed a grey-white to grey-brown endometrial polyp measuring 3.5×2.5 cm, which microscopically showed tumour cells arranged in sheets and in a glandular and papillary pattern with fibrovascular core. IHC for microsatellite instability and p53 were done.